Promising Recent Regenerative Medicine Patents in Plastic and Reconstructive Surgery: Nanotechnology, Structural Fat Grafting, Bone Repair and Regeneration, and Microvascular Surgery - A. Eid, Anas; Ver Halen, Jon P. (Recent Patents on Regenerative Medicine, 2015)
Cosmetic and reconstructive surgery relies extensively on the complex relationship between skin, soft tissue and the underlying bone skeleton. Soft tissue loss and acquired soft tissue deficits are some of the daily challenges faced by the plastic surgeon. Fat grafting has become one of the standard lines of care that has various applications in plastic surgery treatments. The ability of adipose stem cells to rejuvenate tissues is promising for plastic surgery. Bone disorders, including infection and poor healing, pose vexing problems to the reconstructive surgeon. Vascular surgery is a technique necessary for the reconstruction of the most challenging surgical defects, and has great potential for improvement through technology. Recent patents discussed in this article demonstrate promise to dramatically improve a number of specific patient conditions. Nanoscale refinements of current techniques may offer more efficient and improved surgical and non-surgical approaches for reconstruction. Such refinements will significantly expand our capabilities for innovative reconstructive interventions, with high efficiency, specificity and minimal invasiveness.
Keywords: patent